Quality Analysis of Storage Drives - Surve, Rakesh S; Honmane, Vikas N (International Journal of Computer Sciences and Engineering, 2019)
Quality Analysis of Storage Drives is an important thing to be done before actual use of drives in the market. Finding the failure reason of drives and reporting it in an automated way is a challenging work to do. There is no direct solution available to find the actual cause of failure, the cause of failure can be related to drives, firmware, or testing environment. So using various techniques such as drive analysis based upon various parameters of hard disk drive we can predict the cause of failure. Storage drives are important component of any computing devices which needs to be analyzed using different techniques. This paper is an attempt to explore the quality analysis of storage drives.